Synthesis and in vitro Study of Artemisinin/Synthetic Peroxide-Based Hybrid Compounds against SARS-CoV-2 and Cancer - Herrmann, Lars; Yaremenko, Ivan A; Çapcı, Aysun; Struwe, Julia; Tailor, Dhanir; Dheeraj, Arpit; Hodek, Jan; Belyakova, Yulia Yu; Radulov, Peter S; Weber, Jan; Malhotra, Sanjay V; Terent'ev, Alexander O; et al. (ChemMedChem, 2022)
The newly emerged severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) cause life-threatening diseases in millions of people worldwide, in particular, in patients with cancer, and there is an urgent need for antiviral agents against this infection. While in vitro activities of artemisinins against SARS-CoV-2 and cancer have recently been demonstrated, no study of artemisinin and/or synthetic peroxide-based hybrid compounds active against both cancer and SARS-CoV-2 has been reported yet. However, the hybrid drug's properties (e. g., activity and/or selectivity) can be improved compared to its parent compounds and effective new agents can be obtained by modification/hybridization of existing drugs or bioactive natural products. In this study, a series of new artesunic acid and synthetic peroxide based new hybrids were synthesized and analyzed in vitro for the first time for their inhibitory activity against SARS-CoV-2 and leukemia cell lines. Several artesunic acid-derived hybrids exerted a similar or stronger potency against K562 leukemia cells (81-83 % inhibition values) than the reference drug doxorubicin (78 % inhibition value) and they were also more efficient than their parent compounds artesunic acid (49.2 % inhibition value) and quinoline derivative (5.5 % inhibition value). Interestingly, the same artesunic acid-quinoline hybrids also show inhibitory activity against SARS-CoV-2 in vitro (EC50 13-19 μm) and no cytotoxic effects on Vero E6 cells (CC50 up to 110 μM). These results provide a valuable basis for design of further artemisinin-derived hybrids to treat both cancer and SARS-CoV-2 infections.
Keywords: Animals; Antiviral Agents; Peroxides; Chlorocebus aethiops; Quinolines; artemisininy; SARS-CoV-2; antivirové látky; Neoplasms; peroxidy; nádory; farmakoterapie COVID-19; Vero Cells; chinoliny; Artemisinins; lidé; Vero buňky; COVID-19; leukemie; COVID-19 Drug Treatment; Leukemia; Cercopithecus aethiops; zvířata; Humans